Constant pressure Gibbs ensemble Monte Carlo simulations for the prediction of structure I gas hydrate occupancy - Henley, Heath; Lucia, Angelo (Journal of Natural Gas Science and Engineering, 2015)
In this work, constant pressure Gibbs ensemble Monte Carlo (GEMC) simulations were applied as an alternative to grand canonical Monte Carlo (GCMC) simulations to calculate gas hydrate occupancy as function of temperature and pressure. Both rigid and flexible hydrate lattice models were investigated. GEMC structure I methane hydrate occupancy results using the flexible lattice model agree with experimentally measured values and van der Waals-Platteeuw (vdW-P) theory with AAD of 3.67% and 2.68% respectively whereas occupancy results using a rigid lattice model agree with the vdW-P model and literature data with an AAD of 1.02% and 2.78% respectively. The models are validated using occupancy results to predict methane hydrate dissociation pressures. The results compare favorably to previous results and experimental data. An AAD of 0.35% and 0.47% in predicted dissociation temperatures was obtained for the rigid and flexible hydrate lattice models, respectively.